Healthcare considerations for aging people in prisons - Njideka Sanya; Jessica Gaber; Alice Cavanagh; Michelle Howard; Fiona G. Kouyoumdjian (PLoS ONE, 2026)
The number of older adults aged 50 years and above who are incarcerated is increasing rapidly around the world. Providing high quality healthcare for aging incarcerated populations requires tailored services and approaches that consider their unique needs in carceral environments. However, there is limited research on healthcare from the perspective of relevant interest-holders, which challenges the development of interventions to address unmet needs and improve healthcare quality. This study aimed to understand the perspectives of interest-holders on the healthcare considerations of aging prison populations. We carried out secondary reflexive thematic analysis of data from interviews and focus groups with three categories of interest-holders: people with lived experience of incarceration (including people who were incarcerated at the time of data collection), community-based advocates and researchers (including people who work in community organizations, academics, and clinicians), and correctional healthcare providers and leaders. Data were collected from 61 participants between August 2022 and November 2023. We identified four themes: need for better data tracking and comparison, healthcare needs conflict with the carceral environment, physical constraints challenge access to care, and questioning the suitability of older adults for incarceration. This study highlights factors to consider in addressing healthcare for aging incarcerated populations, as described by various individuals with a vested interest in understanding and improving correctional health and health services. Findings can be used to inform ongoing work to improve healthcare and address unmet needs for aging people in prison.